Combination of Autohydrolysis and Catalytic Hydrolysis of Biomass for the Production of Hemicellulose Oligosaccharides and Sugars - Léa Vilcocq; Agnès Crepet; Patrick Jame; Florbela Carvalheiro; Luis C. Duarte (Reactions, 2021)
Three different types of biomass sourced from forestry waste (eucalyptus residues), agricultural waste (wheat straw), and energy crop (miscanthus) were used as starting materials to produce hemicellulosic sugars, furans (furfural and hydroxymethylfurfural), and oligosaccharides. A two-step hybrid process was implemented; biomass was first autohydrolysed without any additive to extract hemicelluloses and dissolve it in water. Then, the hydrolysate was treated with a solid acid catalyst, TiO2-WOx, in order to achieve hydrolysis and produce monomeric sugars and furans. This article investigates the role of the biomass type, autohydrolysis experimental conditions, polymerisation degree and composition of hemicelluloses on the performance of the process coupling autohydrolysis and catalytic hydrolysis. The highest global yields of both oligosaccharides and monomeric sugars were obtained from Eucalyptus (37% and 18%, respectively).